Analysis of Needs for the Development of Nearpod-Based Interactive Learning Media to Improve Student Learning Outcomes in Class XI at SMAN Bengkulu City on Parabolic Motion Material - Guti Ameda Pazah; Eko Risdianto; Andik Purwanto (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
This study set out to examine the demands of educators and learners with reference to the creation of Nearpod application-based learning resources for high school students studying parabolic motion. The information used in this study came from a review of the literature, interviews with physics instructors, and class XI students at SMAN 01, SMAN 03, and SMAN 09 in Bengkulu City. This study employs a qualitative descriptive research methodology. The methods utilized to collect the data are interviews, observations, and literature reviews. Observation and interview sheets made up the research instrument. Qualitative data analysis is used in data analysis procedures. Interactive learning materials are required in classrooms, as indicated by the findings of observations and interviews. This is a result of the fact that professors continue to employ a conventional learning approach and that pupils struggle to understand the information. The usage of interactive learning media in the learning process is necessary as a medium that promotes the learning process, according to the study's findings and discussion.